Characterization of Essential Oils of the Leaves and Fruits of Adenanthera pavonina L. by GC/MS - Mohamed El-Shazly; Mahmoud Mansour; Eman Elsayed; Mohamed Elgindi; Abdel-Nasser Singab (Ain Shams University, 2020)
The characterization of the hydro distilled essential oils of the leaves and fruits of A. pavonina, growing in Egypt, was analyzed by gas chromatography-mass spectrometry (GC-MS) using Rtx-5MS fused bonded column. The results revealed the identification of 27 compounds in the leaves and fruits oils. The leaves oil consisted mainly of monoterpene hydrocarbons (68.01%). The major compounds from the leaves oil were sabinene, accounting for 27.9% of the oil content followed by D-limonene (14.79%), 3-carene (8.46%), caryophyllene (6.57%), and γ-terpinene (6.16%). The fruits oil consisted mainly of sesquiterpene hydrocarbons (62.8%). The major compounds were β-element (39.6%) followed by sabinene (11.7%) and caryophyllene (11.38%). These findings will assist in the differentiation between the volatile oils from different parts of A. pavonina is a step to establish the first monograph for this plant. This study summarized the chemical profiles of A. pavonina leaves and fruits essential oils growing in Egypt for the first time. The leaves essential oils of A. pavonina demonstrated different composition compared with the oils from the fruits.